BCG vaccination induces cross-protective immunity against pathogenic microorganisms. Issue 4 (April 2022) - Soto, Jorge A.; Gálvez, Nicolás M.S.; Andrade, Catalina A.; Ramírez, Mario A.; Riedel, Claudia A.; Kalergis, Alexis M.; Bueno, Susan M.
Abstract : Bacillus Calmette-Guérin (BCG) is an attenuated Mycobacterium bovis strain used as a vaccine to prevent Mycobacterium tuberculosis ( M. tb ) infection. Its ability to potentiate the immune response induced by other vaccines and to promote nonspecific immunomodulatory effects has been described. These effects can be triggered by epigenetic reprogramming and metabolic shifts on innate immune cells, a phenomenon known as trained immunity. The induction of trained immunity may contribute to explain why BCG vaccination effectively decreases disease symptoms caused by pathogens different from M. tb . This article explains the importance of BCG immunization and the possible mechanisms associated with the induction of trained immunity, which might be used as a strategy for rapid activation of the immune system against unrelated pathogens. Highlights: Bacillus Calmette-Guérin (BCG) has been the most widely used vaccine globally to induce immunity against Mycobacterium tuberculosis (M. tb) . This vaccine is an important prophylactic measure to reduce the progression of tuberculous pulmonary disease. BCG is administered, in most cases, during the first days of life and has led to a decrease in neonatal tuberculosis deaths. BCG can promote immunity against other non-tuberculosis mycobacteria, such as Mycobacterium leprae, Mycobacterium ulcerans, Mycobacterium avium, Mycobacterium intracellulare, and Mycobacterium abscessus . BCG can also contribute to the control of opportunistic pathogens. BCG can induce the expansion of T cells that recognize epitopes against other bacteria (different than M. tb ) and viruses [e.g., severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2)]. Although the underlying mechanism for cross-protection is not yet fully understood, it is thought to rely on epigenetic changes and metabolic modifications on immune cells. New data have suggested an association between decreased mortality rates due to SARS-CoV-2 infection with a high rate of BCG vaccination, suggesting that this vaccine might potentially generate cross-protective immunity against this virus, which remains to be robustly tested.